Influence of autonomic control on the specific intermittent performance of judo athletes - Campos, B. T.; Penna, E. M.; Rodrigues, J. G. S.; Diniz, M.; Mendes, T. T.; Filho, A. F. C.; Franchini, E.; Nakamura, F. Y.; Prado, L. S. (Journal of Human Kinetics, 2018)
Judo is a high-intensity intermittent combat sport which causes cardiac adaptations both morphologically and related to the autonomic nervous system (ANS). Therefore, this study aims to verify the correlation between heart rate variability (HRV) at rest with performance in the Special Judo Fitness Test (SJFT) and whether groups with different RR values at rest show different performance in the SJFT and during post-test recovery. Sixteen judo athletes with 7.2 ± 3.9 years of training experience participated in the study. Before and after the SJFT execution HRV and lactate measurements were conducted. For HRV analysis, we used the mean interval RR, the standard deviation of the RR interval (SDNN), the root mean square of successive differences in RR intervals (RMSSD), the low frequency (LF) and high frequency (HF) in normalized and absolute units. The sample was split into two groups (low RR and high RR) to verify if this variable could differentiate between specific performance. For the SDNN, a significant and moderate correlation (r = 0.53) was found with the total number of throws and throws in the series A (r = 0.56) and B (r = 0.54) and for the RMSSD a correlation with throws during series B (r = 0.59) in the SJFT. However, the groups did not differ in performance and recovery. Therefore, HRV is related to intermittent judo performance; however, it cannot differentiate between judokas at different levels of performance.